WHAT HAPPENED IN THE ECOSYSTEM OF THE OKHOTSK SEA IN 2008–2018? - V. P. Shuntov; O. A. Ivanov; K. M. Gorbatenko (Известия ТИНРО)
Critical analysis is done of the main conclusions in the article published by Yury Zuenko and co-authors in this issue of «Izvestia TINRO» journal about changes in the Okhotsk Sea biota in 2008–2018. In that paper, a continuing warming in all layers of the sea is shown quite convincingly, but weight explanations of the observed changes in marine communities and commercial stocks are not offered. Moreover, the authors ignore results of long-term studies of the Okhotsk Sea bioresources conducted from ecosystem positions. From this alternative point of view, some integrated quantitative data on dynamics of zooplankton, zoobenthos, fish, and other biota in the Okhotsk Sea are presented, as well as the schemes of organic matter and energy flows through trophic networks that show a normal functioning of the Okhotsk Sea ecosystem at the present time. On the base of these data, doubts are claimed in correctness of Zuenko’s concept of the ecosystem restructuring in direction to lower productivity and higher efficiency of its functioning.